2004
DOI: 10.1093/epirev/mxh002
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Position and Health among Persons with Diabetes Mellitus: A Conceptual Framework and Review of the Literature

Abstract: FIGURE 1. Conceptual framework for the relation between socioeconomic position and health among persons with diabetes mellitus. Numbers and letters refer to pathways mentioned in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
458
5
18

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 524 publications
(503 citation statements)
references
References 254 publications
(262 reference statements)
22
458
5
18
Order By: Relevance
“…It has been suggested that an accumulation of exposures to multiple unhealthy contextual factors may explain the deleterious health effects of unhealthy neighborhoods. 1,16,33,34 Although the models presented in the current study were adjusted for serious psychological distress, the fact that neighborhood safety was measured using a subjective, individual-level measure suggests that respondents rating their neighborhoods as unsafe are not only living in an unfavorable setting, but are perceiving neighborhood problems and being affected by them. The accumulated burden of these problems may diminish the importance of filling prescriptions or obtaining needed medical treatment promptly in light of competing demands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that an accumulation of exposures to multiple unhealthy contextual factors may explain the deleterious health effects of unhealthy neighborhoods. 1,16,33,34 Although the models presented in the current study were adjusted for serious psychological distress, the fact that neighborhood safety was measured using a subjective, individual-level measure suggests that respondents rating their neighborhoods as unsafe are not only living in an unfavorable setting, but are perceiving neighborhood problems and being affected by them. The accumulated burden of these problems may diminish the importance of filling prescriptions or obtaining needed medical treatment promptly in light of competing demands.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms by which an unfavorable neighborhood environment may impact health behaviors have been proposed, including a lack of access to health-promoting resources, accumulated stress brought on by the presence of hazards in the neighborhood environment, and prevailing attitudes that de-emphasize the importance of health and health behaviors. 1,12,[16][17][18][19] Because the association between neighborhood safety and adherence persisted after adjustment for multiple potential barriers to accessing a pharmacy and paying for prescriptions, including income, insurance status, and access to transportation, the lower adherence observed in unsafe neighborhoods is likely attributable to factors in addition to access and finances. It has been suggested that an accumulation of exposures to multiple unhealthy contextual factors may explain the deleterious health effects of unhealthy neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both individuals from low socioeconomic status and from non-white racial/ethnic groups have poorer control 13 and higher diabetes related morbidity. 14,15 Individuals with poorer health literacy, lower levels of social support and more severe depression also have worse diabetes outcomes. [16][17][18][19] Additionally, the degree of diabetes control is positively associated with the better medication adherence and self-management.…”
Section: Introductionmentioning
confidence: 99%